Ways to strengthen the motivation for good behavior in Quranic verses and Islamic traditions - AliReza Shirzad; mohammad kaviany (اخلاق وحیانی)
One of the ways of formation of Islamic psychology is to solve problems from daily life and find answers based on the teachings of the Qur'an and hadiths; One of the themes of everyday life is motivation; Those who follow the Qur'an can strengthen their positive motivations under the influence of Qur'anic and psychological teachings; The aim of this study was to investigate the methods of strengthening the motivation of desirable behavior in Quranic verses and Islamic traditions and for this purpose, propositions related to this issue were identified and extracted and then examined using qualitative content analysis method. Findings showed that "awareness of the positive characteristics of the individual", "facilitation of action", "generalization of task and action", "perception of moral behavior with self", "action to the extent of power" and "perception of regret and regret" Ineffective ”have been used as methods to strengthen the motivation for desirable behavior in religious sources. Also, the mentioned cases are explained in this article along with their religious documents, and in the path of modeling and using those methods in performing desirable behaviors, examples of the application of those methods in behaviors are also mentioned.